Financial Management in Reaching Product Empowerment Index Standards Related to Science on MSME Performance - Kiki Farida Ferine; Arif Saefudin; Prasetio Ariwibowo; Irfan Azim (Postgraduate, University of Mataram, 2023)
Product innovation has a positive effect on MSME performance. So, product innovation has a positive effect on the performance of MSMEs accepted. Products with interesting and creative innovations will be in demand in the market so that they will improve the performance of MSMEs. A city's economic development requires appropriate action to maximize existing resources through the financial management of MSME actors. One of the solutions to control financial management is to form a UMK Sentra, as a center that can become a forum for its members. Therefore, MSES need to have good financial management to improve their business performance. This study aims to determine the level of effectiveness of financial management at the UMK Center on Jalan Sei Serayu Number 103, Tanjung Rejo, Medan Sunggal District, Medan City, North Sumatra. This study uses qualitative methods through observation and interviews with key informants at MSE centers. From the results of the research, the majority of MSME performance members in Medan City did not experience many obstacles that could affect the growth and sustainability of their business due to the existence of the UMK Sentra group as a center of knowledge for its members. In Medan City, the local government and the MSE Sentra group work well together in managing finances and business. In this study, the system applied to the MSME performance Sentra group in Medan City proved effective in opening opportunities for MSME performance to advance their business and improve their economic welfare to meet the Empowerment index standard. Â